Beyond parental education: Food insecurity, subjective first-generation identity, and mental health in college students - Ezra Mutai; Matthew J. Bauman (Journal of Health Psychology, 2026)
Food insecurity is prevalent among college students and disproportionately burdens first-generation students. This study examined how food insecurity and first-generation identity-operationalized objectively (parental education) and subjectively (self-identification), relate to depression, anxiety, stress, and well-being among 344 students at a mid-sized public university. Food insecurity was the strongest predictor of all four outcomes (partial η 2 = 0.064–0.096, all ps < 0.001). Neither objective nor subjective first-generation status independently predicted symptom severity after accounting for food insecurity. However, subjective first-generation identification significantly predicted food insecurity risk (χ 2 = 9.75, p = 0.002) whereas objective classification did not ( p = 0.088), and survived covariate adjustment (aOR = 1.81, p = 0.015). “Over-identifiers”—students who self-identified as first-generation despite having a college-educated parent—showed the highest food-insecurity prevalence (61.1%). These findings suggest incorporating subjective indicators of first-generation status can better identify at-risk students and inform more equitable mental health interventions within higher education.